Voyageuses occidentales et impérialisme : l’Orient à la croisée des représentations (XIXe siècle) - Isabelle Ernot (Genre & Histoire)
This article explores how gender and imperialism are articulated in the writings of a number of French women travelers to Eastern and Arab countries in the second half of the 19th century. It argues for the role of these Western women travelers in the construction of a discourse that accompanied the process of colonialism and contributed to the defining of social and/or racial hierarchies. The article begins with an examination of the rhetoric used to produce a representation of the oppressed Arab-Muslim woman, in opposition to that of the Western woman. It then examines the travel writers themselves in an effort to discern the origins of the representations they develop.